Stockholm Syndrome as Reflected on Belle in Beauty and the Beast Movie (2017) - Arsiwela Arsiwela (Lembaga Pengembangan Kinerja Dosen, 2024)
The main concern of this study is the stockholm syndrome on Belle. Considering stockholm syndrome is a psychological phenomenon, hence this study uses two theories, namely structural theory and literary psychology. The results of this study concluded that Belle's behavior revealed the individual and situational characteristic of stockholm syndrome. The presence of the stockholm syndrome in this movie harmonizes with the whole plot of Beauty and the Beast. The results of this study concluded that Belle’s behavior shows the individual and situational characteristics of stockholm syndrome. First, Belle developed indicators related to the issue of Stockholm Syndrome which are initial fear and resistance, gradual bonding, positive feelings toward the captor, defending the captor, identifying with the captor's perspective, sacrificing for the captor, internal conflict, and emotional rescue and transformation. Second,the director portrays the issue of stockholm syndrome through characters, events, setting, and style.